Repercussions of COVID-19 on the care and behavior of users of a Child and Adolescent Psychosocial Care Center - Felicialle Pereira da Silva; Taysa do Nascimento Silva; Raphael Alves da Silva; Karina Ferreira da Silva; Ligia Maria de Almeida; Darine Marie Rodrigues da Silva; Jael Maria de Aquino (Universidade Federal do Ceará, 2023)
Objective: to analyze, in the light of Callista Roy's model, the pandemic implications of COVID-19 on the behavior and care of users assisted at a Child and Adolescent Psychosocial Care Center. Methods: a qualitative study, in which 13 family caregivers of users assisted at a Child and Adolescent Psychosocial Care Center participated. Data collection occurred through semi-structured interviews. Data analysis was performed through content analysis. Results: three categories emerged: The impact of social distancing on the behavior of children/adolescents assisted at the Child and Adolescent Psychosocial Care Center; Difficulties experienced by family caregivers with children/adolescents during the COVID 19 pandemic; Welcoming and support for children/adolescents and family members linked to the Child and Adolescent Psychosocial Care Center during the COVID-19 pandemic. Conclusion: children's and adolescents' care and behavior have undergone changes resulting from changes in social interaction and care at the Child and Adolescent Psychosocial Care Center. This scenario required adaptation and, through Callista Roy's model, it was possible to better understand this adaptive process. Contributions to practice: this study allows us to better understand the problem and, consequently, improve the care offered by the team considering the reality presented.